Priamel, Proverb as a Dialogue and Welleryzm in Kashubian Paremiography - Pomierska, Justyna (Poznańskie Studia Slawistyczne, 2015)
The article presents special types of proverbs in Kashubian paremiography: priamel, proverb as a dialogue, welleryzm. These outstanding examples of the proverbial formulas are rarely recorded, usually known locally. The author found in the work of Ceynowa, Rudnicki, Lorentz, Sychta 21 priamels, 4 proverbs as a dialogue and several welleryzms. In addition to the characteristic building is significant that Kashubian priamels and welleryzms for the most part are thematically connected with relationships between man and woman.